2022
DOI: 10.1038/s41598-022-14268-w
|View full text |Cite
|
Sign up to set email alerts
|

Ketone body 3-hydroxybutyrate enhances adipocyte function

Abstract: Ketone bodies, including 3HBA, are endogenous products of fatty acid oxidation, and Hmgcs2 is the first rate-limiting enzyme of ketogenesis. From database analysis and in vivo and in vitro experiments, we found that adipose tissue and adipocytes express Hmgcs2, and that adipocytes produce and secrete 3HBA. Treatment with 3HBA enhanced the gene expression levels of the antioxidative stress factors, PPARγ, and lipogenic factors in adipose tissue in vivo and in adipocytes in vitro, accompanied by reduced ROS leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Hmgcs2, Hmgcl, and Bdh1 are the enzymes that synthesize 3-HB. 44,45 It has been reported that synbiotics increased the expression of synthetic enzymes for 3-HB synthesis in the colons and livers of ASD mice (Fig. 6).…”
Section: Discussionmentioning
confidence: 89%
“…Hmgcs2, Hmgcl, and Bdh1 are the enzymes that synthesize 3-HB. 44,45 It has been reported that synbiotics increased the expression of synthetic enzymes for 3-HB synthesis in the colons and livers of ASD mice (Fig. 6).…”
Section: Discussionmentioning
confidence: 89%
“…Conventionally, ketogenesis occurs primarily in hepatic mitochondria, and ketone bodies are transported into extrahepatic tissues for terminal oxidation. Recently, several studies have revealed the extrahepatic expression of Hmgcs2 and the production of ketone bodies ( 18 , 19 ). Here, we found that the expression of Hmgcs2 was increased slightly in WATs of KD-fed mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When ketogenesis was blocked, KD feeding could not promote adipose expansion, and excess lipid deposition in the blood and liver could not be relieved. Reports have shown that adipocytes express Hmgcs2 and that adipocytes produce and secrete BHB ( 19 ). Here, we found that the KD-induced Hmgcs2 expression in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work identified HMGCS2 as one of the principal stress-regulated genes in elephant seal blubber (Khudyakov et al, 2017;Deyarmin et al, 2019;Pujade Busqueta et al, 2020), but its expression and function in adipose tissue of other mammals has not been studied until very recently. It has now been shown that HMGCS2 is expressed by mature white adipocytes in mouse, which secrete the ketone body 3-hydroxybutyrate (BHB), that, in turn, stimulates expression of genes encoding antioxidant and Frontiers in Physiology frontiersin.org lipogenic enzymes and adipokines (Nishitani et al, 2022). HMGCS2 was also shown to be one of the most highly upregulated genes in human BAT compared to WAT, where it stimulates thermogenesis via production of mevalonate (Balaz et al, 2019).…”
Section: Genes Associated With Metabolism and Neuroendocrine Signalingmentioning
confidence: 99%